Inovasi Pembelajaran Berbasis Modul Interaktif untuk Meningkatkan Pemahaman Mata Pelajaran Aqidah Akhlak Kelas VIII MTs Negeri 11 Jombang - Amrini Shofiyani; Ika Bella Purwandari (ANWARUL, 2025)
The issue of low student engagement and understanding in Aqidah Akhlak learning at MTs Negeri 11 Jombang is attributed to unvaried and unengaging teaching methods. This study aims to develop an innovation-based interactive learning module to enhance eighth-grade students’ conceptual understanding of Aqidah Akhlak. The method used is Research and Development (R&D) with the ADDIE development model, consisting of the stages of analysis, design, development, implementation, and evaluation. The research subjects were 30 eighth-grade students. Validation results indicate that the developed module is highly feasible, with a material expert score of 92.5% and a media expert score of 88.6%. Effectiveness testing showed a significant improvement between the pre-test (average score of 63.07) and post-test (average score of 93.00), with a t-test significance value of 0.000 < 0.05, indicating a significant difference after the use of the module. The average student response questionnaire score reached 96.33%, reflecting a highly positive reception of the module. In conclusion, this interactive module is effective in improving students’ understanding of Aqidah Akhlak concepts. The implications of this study suggest that the development of interactive learning media can serve as an innovative and contextual strategy in Islamic religious education to strengthen students’ comprehensive conceptual understanding.